Lived Experience of Nurse Educators in the Implementation of the CHED Memorandum Order 15, Series of 2017 - Vingson, Carlyl P.; Lachica, Toni-An B.; Parreño, Geraldine T.; Barrientos, Karen Rose B. (Technium Social Sciences Journal, 2026)
This qualitative phenomenological inquiry sought to illuminate the real-world experiences of nurse educators in the implementation of the Commission on Higher Education (CHED) Memorandum Order (CMO) No. 15, series of 2017, which mandates the transition to an Outcomes-Based Education (OBE) framework in all nursing programs across the Philippines. Using purposive sampling, eight nurse educators from a local nursing school in Bacolod City were selected as participants. Data were gathered through in-depth interviews to capture their insights, challenges, and transformative experiences during the implementation process. The study identified four central findings that emerged from the narratives of the participants: (1) Pursuing Excellence in Nursing Education, (2) Recognizing the Valuable Support Received, (3) Transitioning from Competency-Based to Outcomes-Based Education, and (4) Sustaining Nursing Education Through Collaboration. In light of these findings, it is recommended that nursing schools nationwide strengthen institutional mechanisms that promote faculty development, collaboration, and administrative support to ensure the successful and sustainable implementation of OBE.